An image enhancement of s-function based on neighborhood information’ - L.Yang; Suzelawati Zenian; Rozaimi Zakaria (Faculty of Science and Natural Resources, 2020)
Image enhancement is an important field in image processing. In this paper, according to the characteristics of sine function, a new S-function of gray transformation is proposed, and the threshold value and neighborhood standard deviation information are considered at the same time to process the image. Through experiments, the method proposed in this paper has certain application value for image enhancement processing.